Using Generative AI in nursing education: Students’ perceptions - Zuheir N. Khlaif; Nisreen Salameh; Mousa Ajouz; Allam Mousa; Jamil Itmazi; Abdallah Alwawi; Aidah Alkaissi (BMC Medical Education)
Abstract Generative Artificial Intelligence (Gen AI) has brought about a significant transformation in various societal domains, including higher education. It offers a plethora of advantages aimed at enhancing learning outcomes in higher education. This research aimed to examine the factors affecting student performance in nursing when Gen AI is employed in undergraduate nursing programs at Palestinian higher education institutions. A survey was developed based on prior studies, and data were gathered from 517 undergraduate nursing students across various Palestinian higher education institutions. The data were analyzed using Smart PLS. The results indicated that trust in AI positively influences the perceived usefulness of Gen AI and enhances student performance in nursing education. However, the study also noted that AI competencies have a negative impact on student performance. This study's contribution lies in highlighting the critical role of trust in Gen AI in enhancing perceived usefulness and learning outcomes in nursing education. One limitation of this study is its reliance on self-reported instruments, suggesting that future research should consider adopting a mixed-methods and experimental research approach.